PAPS predictive validity in predicting the learning success of master of professional psychology students - Flaviana Rinta Ferdian; Saifuddin Azwar (Jurnal Penelitian dan Evaluasi Pendidikan, 2019)
This study aims to determine the ability of Tes Potensi Akademik Pascasarjana (PAPS Test) in predicting the grade point average (GPA) of the graduate students of the Master of Professional Psychology. PAPS test is the graduate entry requirement test in UGM. Graduate students’ GPA includes semester grade point average (semester GPA), cumulative grade point average (cumulative GPA), grade point average of master courses, and grade point average of professional courses. The data were obtained in the form of PAPS test scores (verbal subtest, reasoning subtest, quantitative subtest, and total score) and the GPA of the graduate students of Master of Professional Psychology of Universitas Gadjah Mada in the class of 2013, 2014, and 2015. The research subjects were 214 students. The analysis was carried out using correlation analysis. The results of the analysis generally indicate that the PAPS test is able to become a predictor of learning success for the graduate students in the Master of Professional Psychology of Universitas Gadjah Mada. The learning success consists of semester GPA, cumulative GPA, GPA of master courses, and GPA of professional courses. If analyzed per subtest, the quantitative subtest has the highest predictive power. On the other hand, the verbal subtest is only a good predictor for GPA of professional courses.